2011
DOI: 10.4061/2011/843591
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine Treatment in Pregnancy: Indications, Efficacy, and Therapeutic Regimen

Abstract: The prevalence of overt and subclinical hypothyroidism during pregnancy is estimated to be 0.3–0.5% and 2–3%, respectively. Thyroid autoantibodies are found in 5–18% of women in the childbearing age. The aim of this review is to underscore the clinical significance of these findings on the health of both the mother and her offspring. Methods of evaluation of thyroid function tests (TFTs) during pregnancy are described as are the threshold values for the diagnosis of overt and subclinical hypothyroidism or hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 85 publications
1
21
0
Order By: Relevance
“…Recently, a European survey found similar results, with 42% of responders screening all pregnant women for thyroid dysfunction [37]. Klubo-Gwiezdzinska et al [38] clearly demonstrated the necessity of updating and promulgating new guidelines for L-T4 treatment during pregnancy.…”
Section: Discussionsupporting
confidence: 51%
“…Recently, a European survey found similar results, with 42% of responders screening all pregnant women for thyroid dysfunction [37]. Klubo-Gwiezdzinska et al [38] clearly demonstrated the necessity of updating and promulgating new guidelines for L-T4 treatment during pregnancy.…”
Section: Discussionsupporting
confidence: 51%
“…One is through the interference in the adaptive mechanisms of the high demand on the thyroid, and the other, through the association with an autoimmune environment with direct effects on the placenta and the fetus as a consequence of the generalized activation of the immune system (220,(255)(256)(257) (D,B,D).…”
Section: What Is the Role Of Thyroid Autoimmunity In Fertility And Prmentioning
confidence: 99%
“…8 Untreated maternal overt hypothyroidism is connected with adverse neonatal outcomes including premature birth, low birth weight, and neonatal respiratory distress. 9 Complications in the pregnancies associated with hypothyroidism are complex and serious, with an important increase of the maternal morbidity, and perinatal morbidity and mortality. 10 Targeted thyroid function testing of only the high-risk group would miss about one third of pregnant women with overt/subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%